Hear the Wind Sing and Pinball - Murakami, Haruki; Tranlated from Japanese by Goosen, Ted (London Vintage Publication, 2015)
"The debut short novels--nearly thirty years out of print-- by the internationally acclaimed writer, newly retranslated and in one English-language volume for the first time, with a new introduction by the author. These first major works of fiction by Haruki Murakami center on two young men--an unnamed narrator and his friend and former roommate, the Rat. Powerful, at times surreal, stories of loneliness, obsession, and eroticism, these novellas bear all the hallmarks of Murakami's later books, giving us a fascinating insight into a great writer's beginnings, and are remarkable works of fiction in their own right. Here too is an exclusive essay by Murakami in which he explores and explains his decision to become a writer. Prequels to the much-beloved classics A Wild Sheep Chase and Dance Dance Dance, these early works are essential reading for Murakami completists and contemporary fiction lovers alike."
Keywords: Young men